Evaluasi Pembelajaran dengan Google Classroom untuk Mengukur Kemampuan Berpikir Kritis - Lutfiyatun, Eka; Kurniati, Depi (An Naba, 2023)
Learning in Nurul Iman Parung Islamic College, especially Kalam Science course, faces new challenges and problems. Students used to evaluated by answering questions related to the opinions of the problems contained in articles sent by Whatsapp application. However, the task directory that is collected is not controlled due to the large number of messages being piled up or files being deleted. As a result, the evaluation process is not optimal. In addition, university students are also required to have good critical thinking. It is necessary to have an evaluation tool that can measure students' critical thinking. This research aims to describe how the implementation of Google Classroom for evaluation and describe how students' critical thinking students. This is descriptive qualitative research with case studies. Data were collected by observation and documentation. The subjects of this study were students in class B of Kalam Science in Akhwal Syakhsiyah, totaling 159 people who were selected by purposive sampling. The results of this study are learning evaluations using Google Classroom to measure students' critical thinking skills are carried out in three stages, namely preparation, implementation, and evaluation. It was concluded that the students in solving the given problems had begun to develop critical thinking skills, as evidenced that the average final score was 82.68.